Pengaruh Pergantian Auditor, Komisaris Independen dan Leverage terhadap Integritas Laporan Keuangan - Dian Widiyati; Yunita Kurnia Shanti (Universitas Pamulang, 2016)
This study aims to analyze and obtain empirical evidence about the effect of auditor switching, independent commissioners and leverage for the integrity of financial statements in property and real estate companies in Indonesia. Independent variables used in this study is auditor switching, independent commissioners and leverage. Dependent variable used in this study is integrity of financial statement was analyzed by conservatism.Study’s sample was property and real estate companies listed in Indonesia Stock Exchange (IDX) period among 2010 – 2014. Data was collected by purposive sampling method. Total 190 data of financial statements companies were taken as study’s sampel. The method of analysis of this research used logistic regression.The result of this research showed that (1) auditor switching did not significantly effect the integrity of financial statements, (2) independent commissioners did not significantly effect the integrity of financial statements, (3) leverage significantly effect the integrity of the financial statements, (4) auditor switching, independent commissioners and leverage significantly effect the integrity of the financial statements.